POLA KETERLIBATAN UNSUR PENTAHELIX DALAM PENGEMBANGAN DESA WISATA (STUDI PADA DESA WISATA TAMBAKSARI, KECAMATAN WANAREJA, CILACAP): - , Ririn Yulianti; Mira Andriani (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2023)
Tambaksari Tourism Village, Wanareja District, Cilacap Regency has various tourism potentials, but the management of tourism potential is still not optimal; improvements are needed in the arrangement of the area. This research aims to explain the phenomenon related to the pattern of involvement of penta-helix elements in the development of the Tambaksari Tourism Village. The method used in the study is the descriptive method with a qualitative approach. Data was collected from 10 informants using purposive sampling techniques for sampling. Data collection techniques use library research and field studies, namely observation and interviews. The research revealed that Tambaksari village only involved business, community, and government. Academics are not yet fully involved, while the media involved is not optimal. Tourism potential can develop if all the multi-parties (pentahelix) in Tambaksari Village, Wanareja District, work together.